(untitled) (Journal of Partial Differential Equations, 2003)
" Some results on the invariant regions ,existence and uniqueness of solutions to a class of integrodifferential systems are established. Applying these results to integrodifferential systems with a small parameter 03b5 > 0, we obtain,in particular, some estimates of solutions uniform in 03b5 > 0."